Kombinasi Proses Anoxide – Oxide Menggunakan Tanaman Kayu Apu (Pistia Stratiotes) untuk Penyisihan COD dan Total Nitrogen Pada Limbah Cair Domestik - Ningrum, Aprilia Putri; Rachmanto, Tuhu Agung (Jurnal Serambi Engineering, 2025)
The increase in population and urbanisation has led to to an increased volume of domestic wastewater containing pollutants such as organic matter and nitrogen, which pose a significant risk to the environment and aquatic ecosystems. This study aims to evaluate the effectiveness of a combined anoxic–oxic process integrated with Pistia stratiotes (water lettuce). constructed wetland system for removing Chemical Oxygen Demand (COD) and total nitrogen from domestic wastewater. The experiment was conducted using wastewater concentrations of 20%, 40% and 60%, with a retention time of five days. The system operated under anoxic conditions for the first two days, This was followed by oxic conditions with aeration from days three to five. The Results showed that the highest removal efficiency was achieved at a wastewater concentration of 20%. wastewater concentration and a five-day retention time. This resulted in COD and total nitrogen removal efficiencies of 63.16% and 70%, respectively. These findings suggest that the anoxic–oxic system combined with Pistia stratiotes is effective in enhancing the treatment performance of domestic wastewater. This is particularly evident at lower concentrations and optimal retention times.